Penerapan Teknologi Biopori Sebagai Upaya Mengurangi Genangan Air di Dusun Baroeh Gampong Jantho Aceh Besar - Zikrillah, Al-Fataya; Yanti, Armida; Octavianty, Asti Farhani; Akbar Cahyadinata, Bimantara; Az-Zahra, Fikriah (Jurnal Riset dan Pengabdian Masyarakat, 2024)
Gampong Jantho is one of the villages that has frequent waterlogging problems. The village is located below a hill range. The southern area of the village, named Dusun Baroeh, is lower than other ones. Additionally, Dusun Baroeh is also isolated from waterways by a road made of concrete and pavement. When rain occurs, Dusun Baroeh always faces waterlogging. Rainwater seepage also transports organic waste and deposits, together with waterlogging. Therefore, one effort to overcome this problem is to create a biopore infiltration hole by utilizing a polymer pipe and organic waste. The implementation of this technology results from a problem-solving perspective through the public opinion pull of villagers, field observations, problem formulation, planning of appropriate technology, and the implementation of biopores. The biopore infiltration holes were placed in six different sites that have frequent waterlogging: three sites in the residents' yards, one site on the footpath, and two sites in the residents' gardens. These biopores work by opening and expanding the water flow from stagnant surfaces to porous soil. This technology is expected to accelerate water infiltration, improve groundwater quality, and reduce stagnant water, which can spread disease.